La parodontite et l’inflammation systémique : à propos d’un cas. - EL IDRISSI El houcine; ASSOUFI Naoufal (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Introduction. Periodontal diseases represent a major public health issue, affecting many individuals and often underdiagnosed due to the absence of early symptoms. The systemic inflammation associated with periodontitis raises concerns about its consequences on overall health. Observation. A 48-year-old female patient presented with a persistent inflammatory syndrome lasting for five months, with no other notable clinical abnormalities except for poor oral hygiene. Examinations revealed an inflammatory syndrome and a panoramic dental X-ray showing bone resorption related to chronic periodontitis. Following antibiotic treatment and extraction of certain teeth, the inflammatory markers normalized. Discussion. Periodontal disease, which is multifactorial, can lead to severe consequences for both oral and general health. The mechanisms of systemic inflammation involve the activation of the innate immune system, with recruitment of neutrophils and increased production of pro-inflammatory cytokines. Systemic complications of periodontitis, such as diabetes and cardiovascular diseases, may occur through direct mechanisms (bacterial invasion) or indirect mechanisms (inflammatory responses). Conclusion. Periodontitis is more than just a simple oral disease; it can cause systemic inflammation and contribute to the development of various systemic pathologies. RÉSUMÉ  Introduction. Les maladies parodontales représentent un enjeu de santé publique majeur, touchant de nombreuses personnes et souvent sous-diagnostiquées en raison de l’absence de symptômes précoces. L’inflammation systémique liée à la parodontite soulève des préoccupations quant à ses conséquences sur la santé générale. Observation. Une patiente de 48 ans a consulté pour un syndrome inflammatoire persistant depuis cinq mois, sans autres anomalies cliniques notables, sauf une mauvaise hygiène bucco-dentaire. Les examens ont révélé un syndrome inflammatoire et un panoramique dentaire montrant une résorption osseuse liée à une parodontite chronique. Après le traitement antibiotique et l’extraction de certaines dents, le bilan inflammatoire s’est normalisé. Discussion. La maladie parodontale, multifactorielle, peut entraîner des conséquences graves sur la santé bucco-dentaire et générale. Les mécanismes d’inflammation systémique impliquent une activation de l’immunité innée, avec un recrutement de polynucléaires neutrophiles et une production accrue de cytokines pro-inflammatoires. Les complications systémiques de la parodontite, telles que le diabète et les maladies cardiovasculaires, peuvent survenir par des mécanismes directs (invasion bactérienne) ou indirects (réponses inflammatoires). Conclusion. La parodontite est plus qu’une simple maladie bucco-dentaire ; elle peut provoquer une inflammation systémique et contribuer au développement de diverses pathologies systémiques.